2020
DOI: 10.1142/s1363919620500784
|View full text |Cite
|
Sign up to set email alerts
|

Individual Innovative Work Behaviour: Effects of Personality, Team Leadership and Climate in the Us Context

Abstract: This paper is the first to empirically investigate the connections between the Big Five personality factors, ambidextrous team leadership, organisational climate of US workers that supports innovation, and individual innovative work behaviour. A self-report survey was used to obtain data from 215 team members in US-based corporations. We provide an empirically tested model of the positive influence of Openness to Experiences, Extraversion and Conscientiousness personality traits on individual innovative work b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
0
10
0
2
Order By: Relevance
“…Therefore, scholars are interested in determining employees' innovative work behavior, which refers to the effort made by an employee to initiate an idea, as well as endorse and implement innovativeness to meet the goals of an individual, team or organization (Janssen, 2000;West and Farr, 1990). Numerous researchers have found that innovative work behavior relies on many factors, including leadership (Javed et al, 2019), big five personality traits (Zuraik et al, 2020) and organizational climate (Imran et al, 2010). Hence, this present study assessed the effect of employees' proactive personalities on innovative work behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, scholars are interested in determining employees' innovative work behavior, which refers to the effort made by an employee to initiate an idea, as well as endorse and implement innovativeness to meet the goals of an individual, team or organization (Janssen, 2000;West and Farr, 1990). Numerous researchers have found that innovative work behavior relies on many factors, including leadership (Javed et al, 2019), big five personality traits (Zuraik et al, 2020) and organizational climate (Imran et al, 2010). Hence, this present study assessed the effect of employees' proactive personalities on innovative work behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The Big Five are extroversion, agreeableness, conscientiousness, emotional stability and openness to experience. Although there is a broad consensus on the value of these character types, it is impossible to directly connect them to IWB without considering several influential variables (Madrid et al, 2013; Woods et al, 2018; Zuraik et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Although there is a broad consensus on the value of these character types, it is impossible to directly connect them to IWB without considering several influential variables (Madrid et al, 2013;Woods et al, 2018;Zuraik et al, 2020).…”
Section: Innovative Work Behaviourmentioning
confidence: 99%
“…Studi tersebut menunjukkan "rencana aksi" sebagai cara yang efisien untuk mencapai tujuan organisasi dan pembuktian kinerja, sehingga menyarankan peran mediasi potensial dari perencanaan tim. Zuraik et al (2019) menyarankan bahwa kerja tim dengan komunikasi yang efisien dapat menghindari kurangnya perencanaan tim kerja dan pada akhirnya mencapai performa tim yang prima.…”
Section: Latar Belakangunclassified
“…Perencanaan tim kerja telah diakui sebagai pendekatan regulasi penting dan proses berbasis tim untuk meningkatkan kinerja tim dosen. Perencanaan adalah keterampilan meta-kognitif penting yang berpengaruh terhadap kinerja organisasi (Zuraik et al, 2019). Tim menggunakan perencanaan sebagai taktik untuk mengoordinasikan berbagai aktivitas rumit, sehingga meningkatkan kinerja mereka.…”
Section: Latar Belakangunclassified